McHale Operation in Patients with Neglected Hip Dislocations: The Importance of Locking Plates. (29th January 2014) - Eidelman, Mark; Katzman, Alexander; Zaidman, Michael; Keren, Yaniv
Abstract : Neglected hip dislocation in patients with cerebral palsy is a challenge for the pediatric orthopedic surgeon. Many patients experience pain, limitation of hip motion, and sitting and hygiene problems. Arthrodesis, proximal femoral head resection, and subtrochanteric valgus osteotomy are effective salvage procedures for patients with painful hip dislocation and restricted hip motion when reconstruction of the hip is not possible. Osteopenia is one of the problems that can complicate the postoperative course in these patients. Postoperative cast immobilization may further worsen the osteopenia and can predispose to fractures of the femur after cast removal. Standard plating of the proximal osteotomy may not always provide adequate stability of the fixation. In order to prevent postoperative osteoporotic fractures we use locking plates, without casting. Since 2003 until 2011, we operated on 9 patients (14 hips) with painful neglected hip dislocations. The first three patients (five hips) were operated on using standard nonlocking plates. All other patients (nine hips) were operated on using locking plates. During the followup, the hardware failed in one of these cases. All patients treated with locking plates had not been casted postoperatively, and none had loss of fixation or fractures during the followup.